Unravelling the myriad physiologic roles of transthyretin: critical considerations for treating transthyretin amyloidosis - Morie A. Gertz; Mandar A. Aras; Nicole Bart; Thomas H. Brannagan; Jan M. Griffin; Amy R. Kontorovich; Andrew M. Rosen (Annals of Medicine)
Background Transthyretin (TTR) is a highly conserved protein with crucial and broadly protective physiologic roles across organ systems and diseases. Evidence shows that TTR contributes to neuroprotection, cognition, glucose regulation, pregnancy, muscle development, and bone mineralization. In several disease states, including diabetes, Alzheimer’s disease, Lewy body dementia, cerebrovascular disease, and osteoporosis, higher TTR levels may be protective. Numerous studies have shown that low levels of TTR are associated with increased mortality overall and in relation to cardiovascular disease and several malignancies.Purpose There is a growing portfolio of approved and investigational transthyretin amyloidosis (ATTR) treatments that differ in their mechanisms and effects on circulating TTR. When selecting an ATTR therapy, clinicians must decide whether to stabilize and preserve TTR and its functions or knockdown and drastically reduce TTR. This review summarizes the vital physiologic roles of TTR in health and disease. We consider the potential effects on normal biologic pathways that may occur while therapeutically suppressing TTR and discuss clinical decisions concerning ATTR therapies in the context of the summarized literature.Discussion TTR is essential for a broad range of physiologic processes and may confer clinically protective effects in neurologic and other organ systems. While a link between low TTR and severe disease and mortality is well established, it remains unclear whether long-term TTR suppression via ATTR therapies increases risk of disease. Clinical decisions in ATTR, however, should reflect the current understanding of the roles of TTR and the patient’s clinical history.Conclusion TTR serves vital physiologic roles across organ systems. Given its clinically protective properties, continued investigation into the potential long-term impact of TTR suppression via knockdown or gene editing therapies is prudent. ATTR treatment selection should reflect an awareness of the physiologic importance of TTR, as well as consideration of the potential long-term impact of chronic TTR suppression.